The Future of Seed Amplification Assays and Clinical Trials - Coysh, Thomas; Mead, Simon (Frontiers in Aging Neuroscience, 2022)
The prion-like seeded misfolding of host proteins, leading to neuronal toxicity, is the leading hypothetical cause of neurodegenerative diseases. Exploitation of the mechanism in the protein misfolding cyclic amplification (PMCA) and real-time quaking induced conversion (RT-QuIC) assays have transformed prion disease research and diagnosis and have steadily become more widely used for research into other neurodegenerative disorders. With the exception of some recent and modest examples, clinical trials in adult neurodegenerative diseases have been expensive, slow and disappointing in terms of clinical benefits. There are several possible explanations: diagnostic errors, co-pathologies, and treatment too late, after irreversible secondary processes of neurodegeneration have become established. The use of protein aggregation assays in clinical trials offers an opportunity to tackle these problems by improving diagnosis of the main pathology and co-pathologies, with highly sensitive detection of aggregation-prone proteopathic seeds in accessible biofluids, enabling very early interventions in those at risk of genetic forms of neurodegeneration. The possibility of quantifying proteopathic seeds is an attractive pharmacodynamic approach to optimise treatments in the preclinical and early clinical stages of drug development. Here we review the potential applications of protein aggregation assays in clinical trials.